Religiuos knowledge in contemporary Indonesia: The contributions of al Washliyah Madrasahs and scholars to the development of hadith studies - Ja’far; Umar Muhammad Noor (Institut Agama Islam Negeri Lhokseumawe, 2024)
This article investigates the role of the Al Jam‘iyatul Washliyah, one of Indonesia’s largest Islamic organizations, in developing hadith studies in the country. This study is based on library research and employs a historical approach. The findings indicate that hadith has been introduced and taught across all Al Washliyah educational institutions from the Dutch colonial period to the present. Several Al Washliyah scholars have published works on hadith studies in both Arabic and Indonesian. Furthermore, the Al Washliyah Fatwa Council, as the organization’s religious authority, acknowledges hadith as the second source of Islamic law. However, it is noted that some fatwas issued by the Council do not heavily rely on the apparent meaning of hadith as a legal reference, but rather refer to established rulings within the Shâfi‘î madhhab.